Hubungan Antara Panjang Tungkai Dengan Kemampuan Sepak Sila dalam Permainan Sepak Takraw siswa kelas XI MAN 1 Kota Gorontalo - Diuli, Mohamad Reza Pratama; Lamusu, Zulkifli; Rival, Muhammad (-, 2026)
The purpose of this study was to determine the relationship between leg length and sepak sila ability in the game of sepak takraw. This study employed a correlational research method using a quantitative approach, which aimed to describe the relationship between leg length and sepak sila ability in sepak takraw among eleventh grade students of MAN 1 Gorontalo City. Based on the results of data analysis, descriptive statistics, hypothesis testing, and discussion, it can be concluded that there is a significant relationship between leg length and sepak sila ability in the game of sepak takraw among eleventh-grade students of MAN 1 Gorontalo City. The data showed that the calculated correlation coefficient (r = 0.695) was greater than the critical value (r = 0.444), indicating a significant relationship between the independent and dependent variables. Therefore, the results of this study confirm that leg length is significantly related to sepak sila ability in the game of sepak takraw among eleventh grade students of MAN 1 Gorontalo City.